An updated patent review of galectin-1 and galectin-3 inhibitors and their potential therapeutic applications (2016–present). (3rd August 2021) - Sethi, Aaftaab; Sanam, Swetha; Alvala, Ravi; Alvala, Mallika
ABSTRACT: Introduction: Galectins are ubiquitous in nature. They have established themselves as a protein family of high therapeutic potential and play a role in a wide variety of diseases like cancer, fibrosis, and Alzheimer's. Within the galectin family, galectin- 1 and galectin- 3 have been widely studied and their roles and functions have now been well established. Areas covered: In this review, we discuss the important advancements in the development of galectin-1 & 3 inhibitors. All patents filed detailing the divergent strategies to inhibit galectin-1 & 3 from 2016 to present have been covered and discussed. Expert opinion: Over the past couple of decades, distinct galectin inhibitors have been synthesized, reported and studied. Among all, the mono and disaccharide-based antagonists have been found to be considerably successful. However, the cumbersome synthetic route followed to develop this class of inhibitors, in addition to complexity involved in making selective modifications within these molecules has posed a significant challenge. Recently, there have been numerous reports on heterocyclic-based galectin inhibitors. If these are established as potent galectin inhibitors, their ease of synthesis and tunability could overcome the potential drawbacks of carbohydrate-based inhibitors and could thus be exploited to develop efficient and highly specific galectin inhibitors.